Serological characteristics of hemolytic transfusion reactions caused by Rh and Kidd antibodies - ZENG Qunjuan; YANG Hecai; LI Xi; QIAN Yulin; JIAO Xin (Zhongguo shuxue zazhi)
[Objective] To retrospectively analyse the serological characteristics of hemolytic transfusion reactions caused by Rh and Kidd antibodies, and to provide reference for safe, timely, and effective blood transfusion. [Methods] Two cases of patients with RhCcEe and Kidd blood type who experienced allogeneic transfusion at Dazhou Central Hospital were selected. A series of immunohematological tests were performed, including ABO, RhDCcEe and Kidd blood typing, unexpected antibody screening and identification, crossmatching, direct antiglobulin test, acid elution test, and capillary centrifugation to separate the patient's own red blood cells from donated red blood cells. [Results] Unexpected antibody screening, antibody identification, and direct antiglobulin test were positive in both patients. Case 1 had anti-Jkb in the plasma, but no specific antibodies were found in the eluate. Case 2 had anti-c and E in the plasma, and anti-E was detected in the eluate. High-speed capillary centrifugation revealed corresponding antigen-positive erythrocytes at the distal end of the blood samples of both patients. [Conclusion] Case 1 received Kidd allogeneic red blood cells, and case 2 received RhCcEe allogeneic red blood cells, and both patients developed the corresponding unexpected antibodies, which led to the occurrence of immune haemolytic blood transfusion reaction.